Involvement of students in school activities in times of COVID-19 pandemic: Actions developed by the IFPA - Campus Paragominas (Research, Society and Development, 2021)
Due to the social isolation resulting from the pandemic caused by COVID-19, the academic community of the Federal Institute of Pará (IFPA) on the Paragominas campus developed remote strategies to minimize the losses of the student routine with the suspension of classroom activities.In this context, this article aims to present the didactic-pedagogical actions that provided the engagement of students enrolled in the institution. The activities of an interactive and elucidative character in the scientific, artistic, cultural and social scope started in may 2020. These were conducted through the social networks facebook, instagram on campus and the digital platform Google Meet. The pedagogical practices carried out made it possible to stimulate, dialogue with students and the production of knowledge.